Aluno com deficiência física: cognições sobre suas habilidades sociais no contexto da educação física escolar - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The literature related to the education of people with disabilities are widely carried out by educators, teachers and other professionals interested in enhancing knowledge for inclusion. However, research into the social skills of people with disabilities is still timid in the context of physical education. These studies have focused on teacher training for action in the inclusive school context. Still others have been concerned with expanding the knowledge repertoire of teachers' social skills to contribute to inclusion. What is noticed is a disadvantage of the research regarding students with physical disabilities and their cognition about their social skills. Social skills are understood as a set of attitudes and behaviors that favor a good social performance and enable a better development of interpersonal relationships. The main authors who supported the theoretical-methodological referential are: Social Skills - Del Prette and Del Prette; Bolsoni-Silva; Fumo et al; Inclusive Physical Education - Aguiar and Duarte; Gorgatti; Souza; Meller and Tesche; and Ferreira and Barreto; of Cognitions - Garrido, Azevedo and Palma; Pajares; and Ribas Jr. We sought to know the cognitions (beliefs, thoughts, perceptions, etc.) of students with physical disabilities included in physical education classes. Research that values the studies of human development contexts and their personal and environmental interactions may be fundamental in the bioecological theory of Urie Bronfenbrenner, so this research has sought, under the lens of this theory, to understand the phenomenon researched here. The participating public were five (5) students with physical disabilities, not wheelchair users and who were in the age group of 11 to 15 years old, attended elementary school II of the 6th to 9th year of five (5) municipal schools of Santarém-Pará. The following instruments were used to collect data: the sociodemographic questionnaire, completed by the parents or guardians, and the semi-structured interview, in which the participants expressed their cognitions. For data analysis, the DSC-Collective Subject Discourse technique was used, which represents the community's opinion on social skills. The relevance of this research is to be an investigation of educational, psychological and evaluative skills of social skills in the inclusive context, differentiating itself by prioritizing the thinking of students with physical disabilities, since it is believed that their cognitions are a tool of self-reflection. and reflection of professionals working with this audience. The results showed that participants recognize and understand their social skills and realize that they are present in the context of physical education classes and that they favor the inclusive context.
Keywords: Aluno com deficiência; Habilidades sociais; Inclusão; FORMAÇÃO HUMANA EM CONTEXTOS FORMAIS E NÃO FORMAIS NA AMAZÔNIA; EDUCAÇÃO